EQCM Analysis of the Insertion Phenomena in a n-Doped Poly-Alkyl-Terthiophene With Regioregular Pattern of Substitution - Dini, Danilo; Salatelli, Elisabetta; Decker, Franco (Frontiers in Chemistry, 2021)
In the present work we have undertaken the study of the n-doping process in poly-3,3′′-didodecyl-2,2′:5′,2′′-terthiophene (poly-33′′-DDTT) employing the electrochemical quartz crystal microbalance (EQCM). The present study aims at the understanding of how cathodic charge in n-doped poly-33′′-DDTT is compensated. For this purpose, the in situ analysis of the variations of the polymeric mass has been considered. Poly-33′′-DDTT was obtained as a thin coating onto a metallic substrate via the anodic coupling of the corresponding monomer 3,3′′-didodecyl-2,2′:5′,2′′-terthiophene (33′′-DDTT). When subjected to electrochemical n-doping in the polarization interval -2.5 ≤ Eappl ≤ 0 V vs Ag/Ag+ the films of poly-33′′-DDTT varied their mass in accordance to a mechanism of cations insertion during n-doping, and cations extraction during polymer neutralization. In fact, the electrochemical doping of polythiophenes requires the accompanying exchange of charged species in order to maintain the electroneutrality within the structure of the polymer in all states of polarization. At the end of a full electrochemical cycle (consisting in the n-doping and the successive neutralization of poly-33′′-DDTT) the polymer retains a fraction of the mass acquired during n-doping thus manifesting phenomena of mass trapping. The combined analysis of electrochemical and microgravimetric data suggest that poly-33′′-DDTT in the n-doped state undergoes (or electrocatalyzes) uncontrolled electrochemical reactions which are not accompanied by mass variations.